Location of fatal prescription opioid-related deaths in 12 states, 2008–2010: Implications for prevention programs. (September 2016) - Easterling, Keith W.; Mack, Karin A.; Jones, Christopher M.
Abstract: Introduction: Prescription opioid pain reliever overdose is a major public health issue in the United States. To characterize the location of drug-related deaths, we examined fatal prescription opioid and illicit drug-related deaths reported in 12 states. Methods: Data are from the Substance Abuse and Mental Health Services Administration's Drug Abuse Warning Network (DAWN). Medical examiners or coroners in 12 states (MA, MD, ME, NH, NM, OK, OR, RI, UT, VA, VT, WV) reported details of state-wide drug-related mortality during 2008–2010. DAWN data included location and manner of death, age, race, and drugs involved. Deaths were coded into three categories: prescription opioid-related, illicit drug-related, and cases that involved both a prescription opioid and an illicit drug. Results: During a 3-year period, there were 14, 091 opioid or illicit drug-related deaths in 12 states. More than half of the prescription opioid-related deaths in all states, except Maryland, occurred at home, rather than in public or in a health care facility. Although it was still the predominant category, lower percentages of illicit drug-related deaths occurred at home. Conclusion: Prescription opioid overdoses have increased substantially, and the location of the person at the time of death can have important public health implications for interventions. Practical applications: This paper highlights that bystander support can be a critical lifesaving factor in drug related deaths but may be more likely for illicit drug-related deaths than for prescription opioid-related deaths.